2021
DOI: 10.1186/s13256-020-02573-9
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of osmotic demyelination syndrome with plasmapheresis: a case report and review of the literature

Abstract: Background Treatment options for chronic osmotic demyelination syndrome are limited to case reports and only a very few show complete recovery. We report a case of complete recovery of chronic osmotic demyelination syndrome with plasmapheresis. Case presentation A 43-year-old Sri Lankan man presented with fever, repeated vomiting, unsteady gait, increased tonicity of his right upper limb and paucity of speech for three days. He was treated in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
(27 reference statements)
0
13
0
1
Order By: Relevance
“…ODS has been reported in human and canine patients following rapid correction of chronic hyponatremia and is associated with transient or permanent neurologic sequelae (1,5,6,10). Dogs at risk of developing ODS include those that undergo rapid correction of chronic hyponatremia secondary to conditions such as intestinal parasitism, hypoadrenal crisis, chronic effusions, or liver dysfunction (5,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ODS has been reported in human and canine patients following rapid correction of chronic hyponatremia and is associated with transient or permanent neurologic sequelae (1,5,6,10). Dogs at risk of developing ODS include those that undergo rapid correction of chronic hyponatremia secondary to conditions such as intestinal parasitism, hypoadrenal crisis, chronic effusions, or liver dysfunction (5,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…One suggested therapy for treatment in the acute phase of ODS is the use of desmopressin and D5W to rapidly relower sodium, suggesting that ODS is reversible for a short period of time, despite neurologic signs already occurring (10,18,31).…”
Section: Discussionmentioning
confidence: 99%
“…Haruyuki Suzukican et al found that minocycline could protect against ODS by inhibiting the activation and accumulation of microglia at the site of demyelinative lesions in a rat model of ODS. Recently, Wijayabandara et al reported a case in which plasmapheresis may remain effective in reversing ODS several weeks after the initial osmotic insult ( 29 ). To our knowledge, the small amount of evidence on the treatment of ODS is based purely on case reports, animal experiments or small case series ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, one canine case study reported that ODS induced whole-body spasms (18), which are automatic jerking movement belonging to a type of seizure (22,23). Prognosis of ODS is variable, and full recovery of neurologic function after ODS could occur with supportive therapy (11,14,24). One human study reported that approximately two third of children affected by ODS were fully recovered from neurologic signs (21).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms from hyponatremia might vary from subtle to severe or even life threatening, so it is important to correct severe hyponatremia immediately (8,10). However, increasing serum sodium level abruptly can cause neurologic complications such as osmotic demyelination syndrome (ODS) and oculomotor abnormalities in humans and dogs (1,2,11).…”
Section: Introductionmentioning
confidence: 99%